A randomized controlled trial of a resilience-based intervention on psychosocial well-being of children affected by HIV/AIDS: Effects at 6- and 12-month follow-up. (October 2017) - Li, Xiaoming; Harrison, Sayward E.; Fairchild, Amanda J.; Chi, Peilian; Zhao, Junfeng; Zhao, Guoxiang
Abstract: Background: Global literature suggests that resilience-based interventions may yield improvements in psychosocial well-being for vulnerable children, but limited data are available regarding the efficacy of such interventions among children affected by parental HIV/AIDS. Objective: To evaluate initial efficacy of a multi-level resilience-based intervention among children affected by parental HIV/AIDS in China in improving children's psychosocial well-being and resilience-related outcomes. Method: Seven hundred-ninety children, 6–17 years of age, were recruited from rural China. Children were either AIDS orphans or were living with one or two parents infected with HIV/AIDS. Children and primary caregivers were randomly assigned to participate in a 4-arm trial to evaluate the Child-Caregiver-Advocacy Resilience (ChildCARE) intervention. This resilience-based psychosocial intervention provides programming at three levels (child, caregiver, community). Survey data were collected at baseline, 6-months, and 12-months in order to examine efficacy of the child-only and child + caregiver arms in improving children's psychological resilience. Results: Intervention groups displayed improvements in several resilience-related outcomes at 6- and 12-month follow-ups, including self-reported coping, hopefulness, emotional regulation, and self-control. The child-only intervention arm showed some fading of intervention effects by 12-months. Conclusion: Preliminary findings suggest that the ChildCARE intervention is efficacious in promoting psychosocial well-being of children affected by parental HIV/AIDS in rural China. Targeting both children and caregivers for psychosocial intervention may be effective in improving children's resilience. Additional evaluation and modifications, including the inclusion of booster sessions, should be considered to further strengthen the program. Highlights: Children affected by HIV face numerous threats to their psychosocial well-being. Resilience-based interventions offer promise for vulnerable youth. We created ChildCARE—a multi-level psychosocial HIV intervention for children. ChildCARE yielded improvements in resilience for children affected by HIV in China.